Elimination behavior and soil mineral nitrogen load in an organic system with lactating sows – comparing pasture-based systems with and without access to poplar (Populus sp.) trees. Issue 6 (3rd July 2019) - Jakobsen, Malene; Hermansen, John Erik; Andersen, Heidi Mai-Lis; Jørgensen, Uffe; Labouriau, Rodrigo; Rasmussen, Jim; Kongsted, Anne Grete
ABSTRACT: Innovative strategies in free-range pig production are needed to improve the environmental performance of the system. Based on previous studies, inclusion of trees was hypothesized to improve the system's nitrogen efficiency. We investigated sow elimination behavior, feces load, and localization as well as soil mineral nitrogen load in pasture-based individual paddocks with and without access to two rows of poplar ( Populus sp .) trees. In contrast to what was expected, sows showed no preference for eliminating in the zone with poplars but clearly avoided defecating near the hut, feed, and water. Soil mineral nitrogen load showed a heterogeneous pattern as also found in previous studies. In comparison to grass, our results indicated that the poplars had an increased winter uptake of nitrate from deeper soil layers.